The Form and Structure of Kentrung Art Performance in Jepara - Dody Candra Harwanto; Sunarto Sunarto (Institut Seni Indonesia Yogyakarta, 2018)
This study aims to analyze the form and structure of Kentrung Art Performance in Ngasem Village, Batealit Sub-district, Jepara. The research method is a descriptive qualitative method with an interpretative case study as the research design. The data were collected by doing the observation, interview, and document study. The data analysis technique was done throughout the process of reduction, presentation, and withdrawal of conclusion (verification). The results of this study indicate that Kentrung musical form consists of two elements of time and elements of melody. For the element of time, Allegretto tempo is used with its speed between 104-112 steps per minute; its meter uses 4/4, in which there are four beats of one-fourth on each bar; and the rhythmic pattern is divided into two sorts (senggakan and sautan) which generally use the value of half tap, and the outcrop rhythm pattern is used for the big terbangan. Most melodies use a half-tone note with the highest tone of G#5 (la), and the lowest tone is F#4 (sol). The musical structure of Kentrung consists of two sentences or periods namely A B which is respectively repeated.